Fatigue crack propagation in underwater carbon fiber reinforced polymer (CFRP)-retrofitted steel panels - Valsangkar, Anuj, author; Mahmoud, Hussam, advisor; Riveros, Guillermo A., committee member; Smith, Frederick W., committee member; Holland, Troy, committee member (Colorado State University. Libraries, 2015)
Steel structures, such as hydraulic structures and ships operate in harsh wet and corrosive environments and can suffer significant deterioration. The deterioration typically manifest itself in the form of corrosion, fatigue cracking, or a combination of both. While these corrosions or cracks are typically viewed as nuisance, if left unrepaid, they can threaten the integrity of the structure. Repairing these fatigue using the conventional repair methods can be proven to not only be time consuming but also ineffective. Recent advances on the use of CFRP to retrofit structures has shown to be a viable solution for increasing fatigue life of structures made of metals such as different types of steels, aluminum, etc. Although large number of studies have been conducted to evaluate the use of CFRP for retrofitting metal alloys and the promising potential of such has been well-demonstrated, the application has been primarily focused on the aerospace and bridge industries. As a result, very few studies have been concerned with retrofitting metallic structures under wet and corrosive environments. With the above mentioned motivations, there is a clear need to conduct studies to evaluate the viability of using CFRP to repair underwater metal structures. To this end, a new experimental setup is devised to allow for underwater testing of large-scale steel panels. The purpose of this experimental study is to provide a first-of-its-kind benchmark data by which the potential for using CFRP for underwater fatigue repairing metallic structures can be assessed. In this study, four large scale steel panels were tested, three of which repaired with CFRP patches, under different environmental conditions (three remaining to be tested for a total of seven specimens). The main focus is evaluate the effect of CFRP on crack growth rate. Since the application in this study is pertain to water navigation structures used in rivers, the effect of fluvial sediments as well as salt are considered in the study. The use of salt allowed for accelerated corrosion in the specimens to represent actual condition of deteriorated panels. The in-air and underwater results showed an increase in fatigue life with use of CFRP in comparison to bare specimens.
Keywords: CFRP; fatigue crack growth; steel; underwater